THE EVENTS OF SUPPORTING AGRICULTURE BY THE STATE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article there is given innovative recommendations about supporting agriculture by the government, improving the life quality of the population, development of the national economy and its integration with the world, strategic directions of government economic policy in agriculture.